Synthesis and Antinociceptive Activity of 5-Amino (N-Substitutedcarboxamide)quinoline Derivatives Targeting TRPV1 Receptor - Ambatkar, Megha Pankaj; Agade, Rishabh Devendra; Khedekar, Pramod Bhujangrao (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Quinoline is a significant heterocyclic moiety involved in several biological activities including inhibition of transient receptor potential vanilloid 1. Materials and Methods A series of 5-amino( N-substituted carboxamide)quinoline derivatives (2o-2t) were synthesized through two steps. FT-IR, 1H NMR and mass spectrum techniques were used to confirm these obtained derivatives. Using acetic acid-induced writhing in rats, all the compounds were tested for TRPV1 inhibition by antinociceptive action. The stomach tissue was investigated by histopathology for checking the ability of synthesized derivatives to damage the stomach mucosa. Also, the biochemical analysis of blood serum was carried out to check the nephrotoxicity and hepatotoxicity. Results All the derivatives (2o-2t) having the dose of 200 mg/kg gave good TRPV1 inhibition by antinociceptive activity. Among all, the derivatives 2q, 2r and 2s had a percentage inhibition of 43.90%, 34.15% and 39.04% respectively when compared with a dose of 100 mg/kg of Ibuprofen (48.78%). Conclusion A novel 5-amino (N -substituted carboxamide) quinoline compounds are shown to be an intriguing place to start for further investigation into potent and reliable TRPV1 inhibitors.
Keywords: Quinoline; Antinociceptive; TRPV1; Acetic acid; Histopathology